Adaptable peer-to-peer internet live media streaming - Biskupski, Bartosz (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2009)
Media streaming is an approach to delivering media, which may consist of video and audio, from a provider to viewers. Media streaming enables simultaneous delivery and playback of media and thus provides an alternative to media download, where the entire media content has to be delivered before the playback can begin. Media streaming can be on-demand for content archived at the provider or live for content produced at the time of delivery.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin.